Design and Development of an E-Marad (Electronic Management Radiology) Application Prototype as an Administrative and Managerial Tool for the Radiology Unit at Hospital B in Jakarta - Ertia Medista; Siti Masrochah; Marsum Marsum; Sudiyono Sudiyono; Ahmad Hariri (Jurnal Syntax Transformation, 2026)
The radiology unit at Hospital B Jakarta still relies on manual administrative processes, leading to inefficiency, errors, and difficulties in data management and reporting. Existing systems like RIS and PACS focus solely on clinical aspects and fail to address these comprehensive managerial needs. This research aims to design, develop, and evaluate a prototype of the Electronic Management Radiology application to improve administrative and managerial efficiency. The study employed a system development approach using the Rapid Application Development (RAD) method, integrating structured techniques and prototyping. Electronic Management Radiology was developed as a web-based platform using the PHP/Laravel framework and MySQL database, designed to unify administrative, managerial, and quality reporting functions. System functionality was evaluated through Black Box Testing by 16 respondents. User acceptance was measured using pre- and post-implementation Technology Acceptance Model (TAM) questionnaires and analyzed using the Wilcoxon Signed Rank Test. Black Box Testing confirmed that all 14 features were functional, with success rates between 87.50% and 100%. TAM evaluation showed a significant increase in user acceptance scores, from a mean of 61.06 before implementation to 81.25 after (33.06% improvement), with a p-value of 0.000 and a very large effect size (Cohen's d = 5.17).  This study successfully developed a prototype that significantly improves user acceptance and system effectiveness. The findings provide a practical and validated model for digitalizing radiology administration that can be adapted by other healthcare facilities to enhance efficiency, data management, and service quality